2008
DOI: 10.21273/hortsci.43.7.1951
|View full text |Cite
|
Sign up to set email alerts
|

Plant Productivity in Response to LED Lighting

Abstract: Light-emitting diodes (LEDs) have tremendous potential as supplemental or sole-source lighting systems for crop production both on and off earth. Their small size, durability, long operating lifetime, wavelength specificity, relatively cool emitting surfaces, and linear photon output with electrical input current make these solid-state light sources ideal for use in plant lighting designs. Because the output waveband of LEDs (single color, nonphosphor-coated) is much narrower than that of traditional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
396
1
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(428 citation statements)
references
References 38 publications
10
396
1
21
Order By: Relevance
“…The spectrum of these artificial lighting systems is often characterized by comparatively wide-band peaks containing small amounts of blue and high amounts of green and red light. Nowadays, light-emitting diodes (LED) providing narrow peaks (some nanometers) with high reproducibility and spectral resolution enable to design optimal species-specific light supply and precise investigation of spectral-dependent plant responses (Massa et al 2008). Currently, most LED systems used for horticultural production in greenhouses (e.g., interlighting modules) provide mainly red and blue light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of these artificial lighting systems is often characterized by comparatively wide-band peaks containing small amounts of blue and high amounts of green and red light. Nowadays, light-emitting diodes (LED) providing narrow peaks (some nanometers) with high reproducibility and spectral resolution enable to design optimal species-specific light supply and precise investigation of spectral-dependent plant responses (Massa et al 2008). Currently, most LED systems used for horticultural production in greenhouses (e.g., interlighting modules) provide mainly red and blue light.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most LED systems used for horticultural production in greenhouses (e.g., interlighting modules) provide mainly red and blue light. Red and blue light, as compared to green light, are the most efficiently absorbed wavelengths by photosynthetic pigments, and provide most energy for photosynthesis (Massa et al 2008). Nevertheless, under strong white light conditions, green light might drive leaf photosynthesis even more efficiently than red light (Terashima et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to produce high-quality crops including sound seedlings as well as uniform crops (Kozai et al, 2004). Light-emitting diodes (LEDs) are a next generation lighting source applied in closed-type plant production systems because their characteristics such as close illumination of plants, small size, and ability to manipulate light quality (Massa et al, 2008). Recent studies related to LEDs have been popular research themes in the production of horticultural crops due to these characteristics (Jeong et al, 2012;Matsuda et al, 2004;Son and Oh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Light-emitting diode (LED) lighting systems have several unique advantages, including the ability to control spectral composition, small size, durability, long operating lifetime, wavelength specificity, relatively cool emitting surfaces, and photon output that is linear with electrical input current. These solid-state light sources are therefore ideal for use in plant lighting designs, and they allow wavelengths to be matched to plant photoreceptors to provide more optimal production and to influence plant morphology and metabolism (Bourget 2008;Massa et al 2008;Morrow 2008). The effects of LED light sources on several plants, such as grape (Puspa et al 2008), strawberry (Nhut et al 2003), banana (Duong et al 2003), maize (Felker et al 1995), potato (Miyashita et al 1995;Jao and Fang 2004), Cymbidium (Tanaka et al 1998), Lilium (Lian et al 2002), Chrysanthemum (Hahn et al 1998;Kim et al 2004;Anzelika et al 2008), Eucalyptus (Nhut et al 2002), Rehmannia glutinose (Hahn et al 2000), Zantedeschia (Jao et al 2005), Euphorbia milii (Dewir et al 2007), Spathiphyllum (Nhut et al 2005), Withania somnifera (Lee et al 2007), and Phalaenopsis orchids (Wongnok et al 2008), have been reported.…”
Section: Introductionmentioning
confidence: 99%